Spectrophotometric and smartphone-based colorimetric methods utilizing polyvinylpyrrolidone-capped silver nanoparticles for determining doxorubicin in human plasma samples - Elmira Behboudi; Saeedeh Khadivi-Derakhshan; Mahtab Pirouzmand; Abolghasem Jouyban; Jafar Soleymani (Scientific Reports)
Abstract Doxorubicin (DOX) or adriamycin is a common anticancer drug with a narrow therapeutic index. Therefore, sensitive and reliable quantification of DOX is crucial for therapeutic drug monitoring purposes. In this study, both a spectrophotometric and a smartphone-based colorimetric method were fabricated to detect DOX in plasma samples. Both methods utilize polyvinylpyrrolidone (PVP)-capped silver nanoplates, which undergo color with varying DOX concentrations. The colorimetric method offers significant beneficial features of fast detection time, simplicity, and the ability to be easily observed by the naked eye without any need for expensive instruments. The linear dynamic ranges are 0.25–5.0 µg/mL and 0.5–5.0 µg/mL, with the lower limit of quantification (LLOQ) of 0.25 and 0.5 µg/mL for spectrophotometric and smartphone image analysis, respectively. The smartphone-based image analysis was performed using a smartphone application (PhotoMetrix), which relies on univariate calibration using the histograms of the RGB image. Using the smartphone camera, the image histograms were automatically generated and processed. The proposed probe can potentially be utilized to detect DOX in clinical samples with a mean accuracy and precision of 88.7% and 3.2%, respectively. The results demonstrated that these methods can accurately determine DOX concentrations in plasma samples, highlighting the potential of integrating digital imagery and smartphone applications with chemometric tools.